Analysis of biology students' problem-solving skills using the PBL model through Lesson Study (LS) online - Wa Ode Nurhawa; Maria Rosalia Ijung Anggur; Raihanah Nur Agustanti; Herawati Susilo; Muntholob Muntholob; Balqis Balqis (Journal of Learning Improvement and Lesson Study, 2021)
Problem-based learning models train students to develop thinking and problem-solving skills in contextual circumstances. This research aims to analyze the problem-solving ability of 32 biology students in 2020 at Malang State University in the course of Plant Physiology. This study is a second-cycle action study using the PBL model through lesson study activities. Data analysis uses a problem-solving skills essay test consisting of identifying problems, identifying strategies, formulating hypotheses, evaluating potential, implementing solutions and evaluating results. The results showed that there was an increase in students' problem-solving ability from cycle I by 60.0% to 72.0% in cycle II and there were several indicators that experienced an increase in scores, namely indicators identifying strategies, formulating hypotheses, implementing solutions, and evaluating results. But the indicator score identifies the problem, and implements the solution decreases.